Influence of plasma electrolytic hardening modes on the structure and properties of 65G steel - Rakhadilov, B; Kozhanova, R. S.; Baizhan, D.; Zhurerova, L. G.; Yerbolatova, G. U.; Kalitova, A.A.; Zhanuzakova, L.N. (Eurasian Journal of Physics and Functional Materials, 2026)
This work presented a study of the structure, hardness and wear resistance of 65G steel treated with electrolyte-plasma hardening under different conditions. The electrolyte-plasma hardening technology and a laboratoryinstallation for the realisation of electrolyte-plasma hardening are also described. After electrolyte-plasmahardening,wehave established thata modifiedlayer consistsofthe a-phase (martensite) and M3C cementite. The study results showed that electrolyte-plasma hardening makes it possible to obtainlayersonthe65G steel surface thatprovidesan increasein microhardnessby2.6 times,wear resistanceby two times,resistance to abrasivewearby1.7 times compared to the original samples. In addition, local hardening ensures the achievement of technical and economic effects due to the absence of the need to isolate an unwanted site of parts, processing only the areas requiring hardening.Recommended CitationRakhadilov, B. K.; Kozhanova, R. S.; Baizhan, D.; Zhurerova, L. G.; Yerbolatova, G. U.; Kalitova, A. A.; and Zhanuzakova, L. N. (2021) "Influence of plasma electrolytic hardening modes on the structure and properties of 65G steel," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 3, Article 6.DOI: https://doi.org/10.32523/ejpfm.2021050306